Huculszczyzna jako "mała ojczyzna" w polskiej świadomości galicyjskiej na przełomie XIX i XX wieku = Huculszczyzna as a homeland in the Galician-Polish awareness at the turn of the 19th century - Lesisz, Ewelina (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article analyses the ways of understanding of the concept of Homeland at the end of the nineteenth century in the Galician region called Huculszczyzna. Writers, ethnographers, artists searched here not only for its exotic character exoticism, but also homeliness and primitive nature.
Keywords: Huculszczyzna; świadomość regionalna; mała ojczyzna; Galicja; 19-20 w.